Analysis of the Effect of Excise Rates Increases, Total Tobacco Production, and Education Level on the Prevalence of Youth Smokers in Indonesia - Noah Van Juanda Siagian; Sri Murwani (Majapahit Journal of Islamic Finance and Management, 2025)
The high prevalence of smoking among individuals aged 15–24 in Indonesia represents a serious issue requiring greater attention, particularly in relation to the effectiveness of fiscal and social policies. This study aims to analyze the impact of excise rate increases, total tobacco production, and education level on youth smoking prevalence in Indonesia. Panel data from 34 provinces for the years 2017, 2019, 2021, and 2023 were utilized. The analytical method employed was panel data regression with a fixed-effect approach, selected based on the results of the Chow and Hausman tests. The findings reveal that, partially, excise rate increases have a negative and significant effect on youth smoking prevalence, while total tobacco production shows no significant effect. Education level exerts a negative and significant influence on youth smoking prevalence. Simultaneously, the three independent variables significantly affect youth smoking prevalence in Indonesia. These results suggest that fiscal policies, such as excise rate increases, alongside improvements in access to education, can serve as effective instruments in reducing smoking prevalence among young people. The study recommends that the government further optimize excise policies and educational programs as strategic measures to control tobacco consumption in Indonesia.